Scale-specific processes underlying the genetic population structure of seabirds in the tropical western Indian Ocean - Danckwerts, Daniel Keith (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Global seabird populations have declined by 70%, since 1950, largely in response to human mediated threats. Identifying the pressures that the remaining populations face has therefore become a top priority. Many breeding colonies are now monitored annually, though others have been almost completely neglected. Considerable bias also exists towards higher latitude species, while fewer studies have been conducted on tropical groups. Beyond tracking population sizes, numerous knowledge gaps also exist that severely restrict conservation efforts. This includes the understanding of seabird meta-population structure and the processes underlying population divergence. The importance of these studies lies in the fact that the preservation of biodiversity requires the conservation of diversification processes. Generating this knowledge is therefore an important first step towards recognising responses to episodic disturbance and long-term environmental change, as well as recovery potential. In this context, the present study employed microsatellite analysis and ringing information to investigate the processes underlying the metapopulation structure of seabirds in the tropical western Indian Ocean. Three species were selected as proxies to cover a range of population sizes, distributional ranges, and intrinsic behavioural (e.g. migratory behaviour) and morphological (e.g. polymorphism) characteristics. These were the Sooty Tern (Onychoprion fuscatus), Red-footed Booby (Sula sula), and Barau's Petrel (Pterodorma baraui). The overall objective was to provide insight into the mechanisms underlying divergence across a range of scales. Microsatellite information highlighted that genetic populations of the Red-footed Booby and Barau's Petrel were weakly, though significantly, structured. For the Barau's Petrel, this was supported by ringing information that indicated extreme colony fidelity. Some gene flow appears to occur among the breeding colonies of the Red-footed Booby, though the scale and frequency of this remains uncertain as banding information is insufficient at this stage. Nevertheless, though populations of both species were genetically structured, the processes underlying divergence were different. Extreme natal philopatry appears to have driven divergence between the two colonies of the Barau's Petrel, while local selective forces (e.g. kleptoparasitism risk and/or selection against immigrants) appear to have isolated the three studied breeding colonies of the Red-footed Booby. Conversely, microsatellite information identified a total lack of genetic structure among breeding colonies of the Sooty Tern in the western Indian Ocean, and between colonies in the western Indian and Eastern Pacific Oceans. This accords with banding recoveries, which illustrate considerable inter-colony exchange of individuals among most islands of the Seychelles and between breeding colonies in the western Indian and West Pacific Oceans. The processes underlying the genetic population structure (or, in this case, lack thereof) in the Sooty Tern therefore appear to operate at extremely large scales. The species' low natal philopatry and high dispersal capabilities, combined with an importance of social stimulation and a reliance on seasonally favourable marine conditions, appears to influence the decisions of where and when individual Sooty Terns choose to breed. Anthropogenic disturbance at breeding sites, particularly that related to egg harvesting activities, also appears to drive dispersal in the Sooty Tern. These results improve our understanding of the mechanisms underlying the genetic population structure in seabirds at low latitudes. However, numerous questions remain unanswered and warrant further study. Clear conservation implications were also identified for the three studied species. Nevertheless, caution should still be applied when extrapolating this information across other species.
Keywords: Sea birds -- Indian Ocean; Sea birds -- Behavior -- Indian Ocean; Sea birds -- Mortality -- Indian Ocean; Sea birds -- Mortality -- Prevention; Sea birds -- Reproduction; Bird declines -- Indian Ocean; Sea birds -- Indian Ocean -- Effect of human beings on; Sooty tern; Red-footed booby; Pterodroma